Efficiency of Islamic and conventional banks in Bangladesh: comparative study using DEA approach - Islam, Sanjida; Kassim, Salina (Islami Bank Training and Research Academy, 2015)
This study involves comparing the efficiency between Islamic and conventional banks in Bangladesh using the Data Envelopment Analysis. It considers 25 commercial banks, of which seven are Islamic, while eighteen are conventional, covering the period from 2009 to 2013.The study finds that the Islamic banks have been pure technically efficient but their scale efficiency is not satisfactory, suggesting that scale inefficiency is the main source of inefficiency of the Islamic banks. In contrast, the conventional banks are found to be pure technically inefficient, but their scale efficiency is satisfactory. The study hopes to contribute towards providing important inputs for the betterment of the banking industry in Bangladesh.